Remote Renewable Hubs for Carbon-Neutral Synthetic Fuel Production - Berger, Mathias; Radu, David; Detienne, Ghislain; Deschuyteneer, Thierry; Richel, Aurore; Ernst, Damien (Frontiers in Energy Research, 2021)
This paper studies the economics of carbon-neutral synthetic fuel production from renewable electricity in remote areas where high-quality renewable resources are abundant. To this end, a graph-based optimisation modelling framework directly applicable to the strategic planning of remote renewable energy supply chains is proposed. More precisely, a graph abstraction of planning problems is introduced, wherein nodes can be viewed as optimisation subproblems with their own parameters, variables, constraints and local objective, and typically represent a subsystem such as a technology, a plant or a process. Edges, on the other hand, express the connectivity between subsystems. The framework is leveraged to study the economics of carbon-neutral synthetic methane production from solar and wind energy in North Africa and its delivery to Northwestern European markets. The full supply chain is modelled in an integrated fashion, which makes it possible to accurately capture the interaction between various technologies on hourly time scales. Results suggest that the cost of synthetic methane production and delivery would be slightly under 200 EUR/MWh and 150 EUR/MWh by 2030 for a system supplying 100 TWh (higher heating value) annually that relies on solar photovoltaic plants alone and a combination of solar photovoltaic and wind power plants, respectively, assuming a uniform weighted average cost of capital of 7%. The cost difference between these system configurations mostly stems from higher investments in technologies providing flexibility required to balance the system in the solar-driven configuration. Synthetic methane costs would drop to roughly 124 EUR/MWh and 87 EUR/MWh, respectively, if financing costs were zero and only technology costs were taken into account. Prospects for cost reductions are also discussed, and options that would enable such reductions are reviewed.